Development of Metal Organic Frameworks (MOFs) Integrated High Performance Batteries - Arafat, Yasir (Curtin University, 2022)
Recharge-able Zn-air batteries (ZABs) are recognized as one of the most promising power sources with lucrative features such as low cost, high energy density, eco-friendliness, and high safety. However, the performance of ZABs is still hampered by the sluggish oxygen redox reactions i.e oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Zeolitic imidazolate frameworks (ZIFs) as a subclass of MOFs are the emerging functional materials, exhibit excellent ORR activity. To supplement the OER activity, ZIFs have been incorporated with OER active materials like BSCF, NiP coating and CoFeNi-LDH using several state-of-the-art strategies. Consequently, the resultant material demonstrated the excellent bi-functional (ORR/OER) activity and outstanding stability even superior to that of precious metal based benchmark (IrO2/Pt-C) catalysts.